Battery cell and electronic device
By using porous current collector and active material layer in the battery cell electrode assembly, the problem of extending the lithium ion transmission path in the existing battery cell is solved, and more efficient lithium ion transmission is achieved, reducing the internal resistance of the battery cell and improving the charge and discharge performance.
Patent Information
- Application Number
- CN202411976886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
In the existing battery cells, non-porous metal foils act as current collectors, resulting in the extension of the transmission path of lithium ions, increasing the internal resistance of the battery cells, and reducing the charge and discharge performance.
A battery cell is designed, and its electrode assembly includes a porous current collector and an active material layer. Lithium ions are in contact with the porous current collector through the active material layer to form multiple transmission paths, and are transmitted in both directions in the active material layer to shorten the transmission distance.
By increasing the transmission path of lithium ions and shortening the transmission distance, the lithium ion transmission dynamics are improved, the internal resistance of the battery cell is reduced, and the charge and discharge performance is improved.
Smart Images

Figure CN119650883A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a battery cell and an electronic device. Background Art
[0002] In existing battery cells, the current collector is usually a non-porous metal foil. During the charge and discharge process, lithium ions cannot pass through the current collector, which will extend the transmission path of lithium ions. This will cause the conduction rate of lithium ions between active particles to decrease, increase the internal resistance of the battery cell, and reduce the charge and discharge performance of the battery cell. Summary of the invention
[0003] In view of the above situation, the present application provides a battery cell, which is beneficial to reducing the internal resistance of the battery cell and improving the charge and discharge performance of the battery cell under the same single-sided coating weight.
[0004] An embodiment of the present application provides a battery cell, which includes an electrode assembly. The electrode assembly includes a first pole piece, a second pole piece and a first diaphragm. The first pole piece includes a first porous current collector and a first active material layer, and the first active material layer is arranged only on one surface of the first porous current collector. The second pole piece has opposite polarity to the first pole piece. The second pole piece includes a second porous current collector and a second active material layer, and the second active material layer is arranged only on one surface of the second porous current collector. The first diaphragm is arranged between the first pole piece and the second pole piece. The thickness of the first porous current collector is T1μm, the thickness of the second porous current collector is T2μm, the thickness of the first diaphragm is T3μm, and 4≤T1+T2+T3≤10.
[0005] During the cycle of the battery cell, lithium ions diffuse in the electrolyte, and the side of the first active material layer away from the first porous current collector and the side provided with the first porous current collector are respectively in contact with the electrolyte to form a lithium ion transmission path, and the side of the second active material layer away from the second porous current collector and the side provided with the second porous current collector are respectively in contact with the electrolyte to form a lithium ion transmission path. Compared with the existing method of using a non-porous metal foil as a current collector, which results in only the side of the active material layer away from the current collector forming a lithium ion transmission path, the number of lithium ion transmission paths can be increased. Moreover, compared with the existing method of using a non-porous metal foil as a current collector, which results in lithium ions being transmitted unidirectionally between the side of the active material layer close to the current collector and the side away from the current collector, lithium ions can be transmitted bidirectionally in the first active material layer and the second active material layer, so as to shorten the transmission distance of lithium ions in the first active material layer and the second active material layer. By increasing the transmission path of lithium ions and shortening the transmission distance of lithium ions, it is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cells using non-porous metal foils, the internal resistance of the battery cells can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cells can be improved. By limiting 4≤T1+T2+T3≤10, it is convenient to improve the structural strength of the electrode assembly and shorten the transmission distance of lithium ions in the first porous current collector, the second porous current collector and the first separator, which is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cells using non-porous metal foils, the internal resistance of the battery cells can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cells can be improved.
[0006] In some embodiments of the present application, 0.5≤T1≤3, so as to improve the structural strength of the first porous current collector and shorten the transmission distance of lithium ions in the first porous current collector, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved.
[0007] In some embodiments of the present application, 0.5≤T2≤3, so as to improve the structural strength of the second porous current collector and shorten the transmission distance of lithium ions in the second porous current collector, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved.
[0008] In some embodiments of the present application, 3≤T3≤5, so as to improve the isolation stability of the first diaphragm and shorten the transmission distance of lithium ions in the first diaphragm, which is beneficial to improving the lithium ion transmission dynamics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved.
[0009] In some embodiments of the present application, 4≤T1+T2+T3≤8, so as to further shorten the transmission distance of lithium ions in the first porous current collector, the second porous current collector and the first separator, which is beneficial to further improve the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be further improved.
[0010] In some embodiments of the present application, 0.5≤T1≤2, so as to further shorten the transmission distance of lithium ions in the first porous current collector, which is beneficial to further improve the charge and discharge performance of the battery cell.
[0011] In some embodiments of the present application, 0.5≤T2≤2, so as to further shorten the transmission distance of lithium ions in the second porous current collector, which is beneficial to further improve the charge and discharge performance of the battery cell.
[0012] In some embodiments of the present application, 3≤T3≤4, so as to further shorten the transmission distance of lithium ions in the first separator, which is beneficial to further improve the charge and discharge performance of the battery cell.
[0013] In some embodiments of the present application, the material of the first porous current collector includes copper, the material of the second porous current collector includes aluminum, and 1≤T2 / T1≤1.6, so as to match the heat dissipation capacity of the internal resistance of the first pole piece and the second pole piece.
[0014] In some embodiments of the present application, the porosity of the first porous current collector is 20% to 40%, and the average pore size of the pores of the first porous current collector is D1, 5μm≤D1≤20μm, so as to reduce the resistance of lithium ions passing through the first porous current collector and help improve the structural strength of the first porous current collector.
[0015] In some embodiments of the present application, the porosity of the second porous current collector is 20% to 40%, and the average pore size of the pores of the second porous current collector is D2, 5μm≤D2≤20μm, so as to reduce the resistance of lithium ions passing through the second porous current collector and help to improve the structural strength of the second porous current collector.
[0016] In some embodiments of the present application, the electrode assembly further includes a second diaphragm. The first electrode sheet, the first diaphragm, the second electrode sheet and the second diaphragm are stacked and wound in sequence to form the electrode assembly, and 4≤T1+T2+T3≤10 is conducive to reducing the thickness of the electrode assembly.
[0017] In some embodiments of the present application, the electrode assembly further includes a second diaphragm. The second diaphragm, the first pole piece, the first diaphragm and the second pole piece are sequentially stacked and wound to form the electrode assembly, and 4≤T1+T2+T3≤10 is conducive to reducing the thickness of the electrode assembly.
[0018] In some embodiments of the present application, the electrode assembly further includes a second diaphragm. The first electrode sheet, the first diaphragm, and the second electrode sheet are stacked in sequence to form a repeating unit. A plurality of repeating units are stacked in sequence to form an electrode assembly, and a second diaphragm is disposed between two adjacent repeating units, and 4≤T1+T2+T3≤10 is conducive to reducing the thickness of the electrode assembly.
[0019] In some embodiments of the present application, along the thickness direction of the electrode assembly, the first diaphragm is arranged between the first active material layer and the second active material layer, a lithium ion transmission path is formed between the first active material layer and the second active material layer, a lithium ion transmission path is formed between one side of the first active material layer having a first porous current collector and another second electrode sheet, and a lithium ion transmission path is formed between one side of the second active material layer having a second porous current collector and another first electrode sheet.
[0020] In some embodiments of the present application, along the thickness direction of the electrode assembly, the first diaphragm is arranged between the first porous current collector and the second active material layer, a lithium ion transmission path is formed between the side of the first active material layer where the first porous current collector is provided and the side of the second active material layer where the second porous current collector is provided, a lithium ion transmission path is formed between the side of the first active material layer facing away from the first porous current collector and the other second electrode sheet, and a lithium ion transmission path is formed between the side of the second active material layer facing away from the second porous current collector and the other first electrode sheet.
[0021] In some embodiments of the present application, along the thickness direction of the electrode assembly, the first diaphragm is arranged between the first active material layer and the second porous current collector, a lithium ion transmission path is formed between the first active material layer on one side of which the first porous current collector is provided and the second active material layer, a lithium ion transmission path is formed between the first active material layer on one side away from the first porous current collector and the other second electrode sheet, and a lithium ion transmission path is formed between the second active material layer on one side of which the second porous current collector is provided and the other first electrode sheet.
[0022] In some embodiments of the present application, along the thickness direction of the electrode assembly, the first diaphragm is arranged between the first porous current collector and the second porous current collector, a lithium ion transmission path is formed between the second active material layer on one side of which the second porous current collector is provided and the first active material layer, a lithium ion transmission path is formed between the first active material layer on one side of which the first porous current collector is provided and the other second electrode sheet, and a lithium ion transmission path is formed between the second active material layer on one side away from the second porous current collector and the other first electrode sheet.
[0023] In some embodiments of the present application, the first diaphragm includes a first porous substrate layer and an adhesive layer disposed on at least one surface of the first porous substrate layer, and the first diaphragm forms a composite with the first porous current collector and / or the second porous current collector through the adhesive layer. The composite can be subjected to coating, cold pressing, winding and other processes as a whole, and the composite has better structural strength than a single current collector or diaphragm, and the total thickness of the current collector and the diaphragm can be reduced while meeting the structural strength requirements.
[0024] In some embodiments of the present application, the thickness of the composite is T4 μm, 4≤T4≤10, so as to improve the structural strength of the electrode assembly and shorten the transmission distance of lithium ions in the first porous current collector, the second porous current collector and the first separator, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved.
[0025] In some embodiments of the present application, the tensile strength of the composite body along the width direction of the composite body is S1,160kgf / cm 2 ≤S1≤500kgf / cm 2 , in order to improve the structural stability of the composite, facilitate the processing of the composite as a whole, and reduce the risk of excessive adhesive clogging the pores and causing the lithium ion transmission path to fail.
[0026] In some embodiments of the present application, the tensile strength of the composite body along the length direction of the composite body is S2, 160kgf / cm 2 ≤S2≤500kgf / cm 2 , in order to improve the structural stability of the composite, facilitate the processing of the composite as a whole, and reduce the risk of excessive adhesive clogging the pores and causing the lithium ion transmission path to fail.
[0027] In some embodiments of the present application, the first porous substrate layer includes at least one of polypropylene, polyethylene, polyethylene terephthalate, and polyimide. The porosity of the first porous substrate layer is 30% to 45%, so as to improve the liquid retention capacity of the first diaphragm, reduce the resistance of lithium ions passing through the first diaphragm, and help improve the structural strength of the first diaphragm.
[0028] In some embodiments of the present application, T1+T3≥4, so that when the first separator forms a composite with the first porous current collector through the adhesive layer, the composite meets the structural strength requirements of the processing procedure as a whole.
[0029] In some embodiments of the present application, T2+T3≥4, so that the first separator 40 forms a composite with the second porous current collector through the adhesive layer 42, so that the composite meets the structural strength requirements of the processing steps as a whole.
[0030] An embodiment of the present application further provides an electronic device, which includes any one of the battery cells in the above embodiments.
[0031] In the above-mentioned battery cell and electronic device, by increasing the transmission path of lithium ions and shortening the transmission distance of lithium ions, it is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cell using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved. By limiting 4≤T1+T2+T3≤10, it is convenient to improve the structural strength of the electrode assembly and shorten the transmission distance of lithium ions in the first porous current collector, the second porous current collector and the first separator, which is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cell using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a structural schematic diagram of the arrangement of the first pole piece and the second pole piece of a battery cell in one embodiment of the present application.
[0033] Figure 2 It is a schematic diagram of the first winding structure of the electrode assembly of the battery cell in one embodiment of the present application.
[0034] Figure 3 It is a schematic diagram of the second winding structure of the electrode assembly of the battery cell in one embodiment of the present application.
[0035] Figure 4 It is a schematic diagram of the third winding structure of the electrode assembly of the battery cell in one embodiment of the present application.
[0036] Figure 5 It is a schematic diagram of the structure of a repeating unit of a battery cell in one embodiment of the present application.
[0037] Figure 6 It is a structural schematic diagram of the arrangement of the first pole piece and the second pole piece of a battery cell in one embodiment of the present application.
[0038] Figure 7 It is a structural schematic diagram of the arrangement of the first pole piece and the second pole piece of the battery cell in another embodiment of the present application.
[0039] Figure 8 It is a first structural schematic diagram of a battery cell complex in one embodiment of the present application.
[0040] Fig. 9It is a second structural schematic diagram of a battery cell complex in one embodiment of the present application.
[0041] Fig.10 It is a third structural schematic diagram of a battery cell complex in another embodiment of the present application.
[0042] Fig.11 It is a schematic diagram of the structure of an electronic device in one embodiment of the present application.
[0043] Main component symbols Battery Cell 100 Electronic device 200 Electrode assembly 10 Repeating unit 10A Complex 10B First pole piece 20 The first porous current collector 21 First aperture 21A First active material layer 22 The second pole piece 30 The second porous current collector 31 Second aperture 31A Second active material layer 32 The first diaphragm 40 The first porous substrate layer 41 Adhesive layer 42 Second diaphragm 50 Lithium Ion + The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0045] It should be noted that when an element is considered to be "connected" to another element, it may be directly connected to the other element or there may be a centrally disposed element at the same time. When an element is considered to be "disposed" on another element, it may be directly disposed on the other element or there may be a centrally disposed element at the same time.
[0046] When a value is considered to be "equal" to another value, it means that the two are equal within the set deviation, and the set deviation range is within 5%. In other words, when at least one of the two values fluctuates within the set deviation range, even if their values are not equal, they are still judged to be roughly equal. When a value is considered to have a ratio of "1:1" to another value, it means that the two are equal within the set deviation, and the set deviation range is within 5%. In other words, when at least one of the two values fluctuates within the set deviation range, even if their values are not equal, they are still judged to be equal in ratio.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0048] An embodiment of the present application provides a battery cell, which includes an electrode assembly. The electrode assembly includes a first pole piece, a second pole piece and a first diaphragm. The first pole piece includes a first porous current collector and a first active material layer, and the first active material layer is arranged only on one surface of the first porous current collector. The second pole piece has opposite polarity to the first pole piece. The second pole piece includes a second porous current collector and a second active material layer, and the second active material layer is arranged only on one surface of the second porous current collector. The first diaphragm is arranged between the first pole piece and the second pole piece. The thickness of the first porous current collector is T1μm, the thickness of the second porous current collector is T2μm, the thickness of the first diaphragm is T3μm, and 4≤T1+T2+T3≤10.
[0049] In the above-mentioned battery cell, by increasing the transmission path of lithium ions and shortening the transmission distance of lithium ions, it is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cell using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved. By limiting 4≤T1+T2+T3≤10, it is convenient to improve the structural strength of the electrode assembly and shorten the transmission distance of lithium ions in the first porous current collector, the second porous current collector and the first separator, which is beneficial to improve the lithium ion transmission dynamics. Compared with the existing battery cell using non-porous metal foil, the internal resistance of the battery cell can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell can be improved.
[0050] The embodiments of the present application are further described below in conjunction with the accompanying drawings.
[0051] See also Figure 1An embodiment of the present application provides a battery cell 100, which is applied to a secondary battery. A secondary battery refers to a battery that can be continuously used by activating active materials by charging after the battery is discharged.
[0052] The battery cell 100 includes an electrode assembly 10 for converting chemical energy into electrical energy. The electrode assembly 10 includes a first electrode sheet 20 , a second electrode sheet 30 and a first separator 40 .
[0053] The first electrode sheet 20 includes a first porous current collector 21 and a first active material layer 22, and the first active material layer 22 is disposed only on one surface of the first porous current collector 21. The first porous current collector 21 has first pores 21A and is configured to allow electrolyte to penetrate.
[0054] The second electrode sheet 30 has a polarity opposite to that of the first electrode sheet 20. The second electrode sheet 30 includes a second porous current collector 31 and a second active material layer 32, and the second active material layer 32 is disposed only on one surface of the second porous current collector 31. The second porous current collector 31 has second pores 31A configured to allow electrolyte penetration.
[0055] The first diaphragm 40 is disposed between the first pole piece 20 and the second pole piece 30 , and the first diaphragm 40 is used to separate the first pole piece 20 from the second pole piece 30 .
[0056] During the cycle of the battery cell 100, lithium ions diffuse in the electrolyte, and the side of the first active material layer 22 away from the first porous current collector 21 and the side provided with the first porous current collector 21 are respectively in contact with the electrolyte to form a lithium ion transmission path (see Li + In the direction of the arrow, the side of the second active material layer 32 away from the second porous current collector 31 and the side provided with the second porous current collector 31 are respectively in contact with the electrolyte to form a lithium ion transmission path, which can increase the number of lithium ion transmission paths compared with the existing method of using a non-porous metal foil as a current collector, resulting in only the side of the active material layer away from the current collector forming a lithium ion transmission path. In addition, compared with the existing method of using a non-porous metal foil as a current collector, resulting in lithium ions being transmitted unidirectionally between the side of the active material layer close to the current collector and the side away from the current collector, lithium ions can be bidirectionally transmitted in the first active material layer 22 and the second active material layer 32, so as to shorten the transmission distance of lithium ions in the first active material layer 22 and the second active material layer 32.
[0057] By increasing the transmission path of lithium ions and shortening the transmission distance of lithium ions, the lithium ion transmission dynamics are improved. Compared with the existing battery cells using non-porous metal foils, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, thereby improving the charge and discharge performance of the battery cell 100.
[0058] Please continue reading Figure 1 , the thickness of the first porous current collector 21 is T1μm, the thickness of the second porous current collector 31 is T2μm, the thickness of the first separator 40 is T3μm, and 4≤T1+T2+T3≤10. When T1+T2+T3 is too small (<4), the structural strength of the electrode assembly 10 is likely to be weak; when T1+T2+T3 is too large (>10), the transmission distance of lithium ions in the first porous current collector 21, the second porous current collector 31 and the first separator 40 is likely to be extended, resulting in an increase in the internal resistance of the battery cell 100. By limiting 4≤T1+T2+T3≤10, the structural strength of the electrode assembly 10 can be improved, and the transmission distance of lithium ions in the first porous current collector 21, the second porous current collector 31 and the first separator 40 can be shortened, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0059] Optionally, T1+T2+T3 is one of 4, 5, 6, 7, 8, 9, 10 and any other value in the range of 4≤T1+T2+T3≤10.
[0060] Furthermore, 4≤T1+T2+T3≤8, so as to further shorten the transmission distance of lithium ions in the first porous current collector 21, the second porous current collector 31 and the first separator 40, which is beneficial to further improve the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be further improved.
[0061] Please continue reading Figure 1 In some embodiments, 0.5≤T1≤3, so as to improve the structural strength of the first porous current collector 21 and shorten the transmission distance of lithium ions in the first porous current collector 21, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foils, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0062] Optionally, T1 is one of 0.5, 1, 1.5, 2, 2.5, 3 and any other value in the range of 0.5≤T1≤3.
[0063] Furthermore, 0.5≤T1≤2, so as to further shorten the transmission distance of lithium ions in the first porous current collector 21, which is beneficial to further improve the charge and discharge performance of the battery cell 100.
[0064] Please continue reading Figure 1In some embodiments, 0.5≤T2≤3, so as to improve the structural strength of the second porous current collector 31 and shorten the transmission distance of lithium ions in the second porous current collector 31, which is beneficial to improving the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0065] Optionally, T2 is one of 0.5, 1, 1.5, 2, 2.5, 3 and any other value in the range of 0.5≤T2≤3.
[0066] Furthermore, 0.5≤T2≤2, so as to further shorten the transmission distance of lithium ions in the second porous current collector 31, which is beneficial to further improve the charge and discharge performance of the battery cell 100.
[0067] Please continue reading Figure 1 In some embodiments, 3≤T3≤5, so as to improve the isolation stability of the first separator 40 and shorten the transmission distance of lithium ions in the first separator 40, which is beneficial to improving the lithium ion transmission dynamics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0068] Optionally, T3 is one of 3, 3.5, 4, 4.5, 5 and any other value in the range of 3≤T3≤5.
[0069] Furthermore, 3≤T3≤4, so as to further shorten the transmission distance of lithium ions in the first separator 40 , which is beneficial to further improve the charge and discharge performance of the battery cell 100 .
[0070] Please continue reading Figure 1 In some embodiments, the material of the first porous current collector 21 includes copper, and the material of the second porous current collector 31 includes aluminum. Copper has better electrical conductivity and thermal conductivity than aluminum, 1≤T2 / T1≤1.6, so as to match the impedance and heat dissipation capacity of the first pole piece 20 and the second pole piece 30.
[0071] Optionally, T2 / T1 is one of 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 and any other value in the range of 1≤T2 / T1≤1.6.
[0072] In some embodiments, the porosity of the first porous current collector 21 is 20% to 40%, and the average pore size of the pores of the first porous current collector 21 is D1 μm, 5≤D1≤20, so as to reduce the resistance of lithium ions passing through the first porous current collector 21 and help improve the structural strength of the first porous current collector 21.
[0073] Optionally, D1 is one of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and any other value in the range of 5≤D1≤20.
[0074] In some embodiments, the porosity of the second porous current collector 31 is 20% to 40%, and the average pore size of the pores of the second porous current collector 31 is D2 μm, 5≤D2≤20, so as to reduce the resistance of lithium ions passing through the second porous current collector 31 and help improve the structural strength of the second porous current collector 31.
[0075] Optionally, D2 is one of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and any other value in the range of 5≤D2≤20.
[0076] See also Figure 2 In some embodiments, the electrode assembly 10 further includes a second separator 50. The first electrode sheet 20, the first separator 40, the second electrode sheet 30, and the second separator 50 are sequentially stacked and wound to form the electrode assembly 10. By 4≤T1+T2+T3≤10, it is beneficial to reduce the thickness of the electrode assembly 10. Optionally, the first separator 40 is disposed between the first porous current collector 21 and the second porous current collector 31.
[0077] See also Figure 3 In some embodiments, the electrode assembly 10 further includes a second separator 50. The second separator 50, the first electrode sheet 20, the first separator 40 and the second electrode sheet 30 are sequentially stacked and wound to form the electrode assembly 10. By 4≤T1+T2+T3≤10, it is beneficial to reduce the thickness of the electrode assembly 10. Optionally, the first separator 40 is disposed between the first porous current collector 21 and the second active material layer 32.
[0078] See also Figure 4 In some embodiments, the electrode assembly 10 further includes a second separator 50. The second separator 50, the first electrode sheet 20, the first separator 40, and the second electrode sheet 30 are sequentially stacked and wound to form the electrode assembly 10. By 4≤T1+T2+T3≤10, it is beneficial to reduce the thickness of the electrode assembly 10. Optionally, the first separator 40 is disposed between the first active material layer 22 and the second active material layer 32.
[0079] See also Figure 5In some embodiments, the electrode assembly 10 further includes a second diaphragm 50. The first electrode sheet 20, the first diaphragm 40, and the second electrode sheet 30 are stacked in sequence to form a repeating unit 10A. A plurality of repeating units 10A are stacked in sequence to form the electrode assembly 10, and a second diaphragm 50 is disposed between two adjacent repeating units 10A. By 4≤T1+T2+T3≤10, it is beneficial to reduce the thickness of the electrode assembly 10.
[0080] See also Figure 6 In some embodiments, along the thickness direction of the electrode assembly 10, the first separator 40 is arranged between the first active material layer 22 and the second active material layer 32, a lithium ion transmission path is formed between the first active material layer 22 and the second active material layer 32, a lithium ion transmission path is formed between one side of the first active material layer 22 having the first porous current collector 21 and the other second electrode sheet 30, and a lithium ion transmission path is formed between one side of the second active material layer 32 having the second porous current collector 31 and the other first electrode sheet 20.
[0081] Please continue reading Figure 6 In some embodiments, along the thickness direction of the electrode assembly 10, the first separator 40 is arranged between the first porous current collector 21 and the second porous current collector 31, a lithium ion transmission path is formed between the side of the first active material layer 22 provided with the first porous current collector 21 and the side of the second active material layer 32 provided with the second porous current collector 31, a lithium ion transmission path is formed between the side of the first active material layer 22 facing away from the first porous current collector 21 and the other second electrode sheet 30, and a lithium ion transmission path is formed between the side of the second active material layer 32 facing away from the second porous current collector 31 and the other first electrode sheet 20.
[0082] See also Figure 7 In some embodiments, along the thickness direction of the electrode assembly 10, the first diaphragm 40 is arranged between the first porous current collector 21 and the second active material layer 32, a lithium ion transmission path is formed between the first active material layer 22 on one side of the first porous current collector 21 and the second active material layer 32, a lithium ion transmission path is formed between the first active material layer 22 on one side away from the first porous current collector 21 and the other second electrode sheet 30, and a lithium ion transmission path is formed between the second active material layer 32 on one side of the second porous current collector 31 and the other first electrode sheet 20.
[0083] Please continue reading Figure 7In some embodiments, along the thickness direction of the electrode assembly 10, the first separator 40 is arranged between the first active material layer 22 and the second porous current collector 31, a lithium ion transmission path is formed between the second active material layer 32 on one side of the second porous current collector 31 and the first active material layer 22, a lithium ion transmission path is formed between the first active material layer 22 on one side of the first porous current collector 21 and the other second electrode sheet 30, and a lithium ion transmission path is formed between the second active material layer 32 on one side away from the second porous current collector 31 and the other first electrode sheet 20.
[0084] See also Figure 8 , Fig. 9 and Fig.10 In some embodiments, the first diaphragm 40 includes a first porous substrate layer 41 and an adhesive layer 42 disposed on at least one surface of the first porous substrate layer 41, and the first diaphragm 40 forms a composite body 10B with the first porous current collector 21 and / or the second porous current collector 31 through the adhesive layer 42. Optionally, the first diaphragm 40 forms a composite body 10B with the first porous current collector 21 and the second porous current collector 31 through the adhesive layer 42, or the first diaphragm 40 forms a composite body 10B with the first porous current collector 21 through the adhesive layer 42, or the first diaphragm 40 forms a composite body 10B with the second porous current collector 31 through the adhesive layer 42.
[0085] Conventional separators and current collectors need to be rolled separately and undergo coating, cold pressing, winding and other processes, so they have structural strength requirements for each. The thickness of the separator is generally not less than 5μm, the thickness of the negative electrode current collector is generally not less than 4μm, the thickness of the positive electrode current collector is generally not less than 6μm, and the total thickness of the current collector and separator is not less than 15μm. The composite 10B can undergo coating, cold pressing, winding and other processes as a whole. Compared with a single current collector or separator, the composite 10B has better structural strength, and the total thickness of the current collector and separator can be thinned while meeting the structural strength requirements.
[0086] In some embodiments, the thickness of the composite 10B is T4 μm, 4≤T4≤10, so as to improve the structural strength of the electrode assembly 10 and shorten the transmission distance of lithium ions in the first porous current collector 21, the second porous current collector 31 and the first separator 40, which is beneficial to improve the lithium ion transmission kinetics. Compared with the existing battery cells using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0087] Optionally, T4 is one of 4, 5, 6, 7, 8, 9, 10 and any other value in the range of 4≤T4≤10.
[0088] Furthermore, 4≤T4≤8, so as to further shorten the transmission distance of lithium ions in the first porous current collector 21 , the second porous current collector 31 and the first separator 40 , which is beneficial to further improve the charge and discharge performance of the battery cell 100 .
[0089] See also Fig. 9 In some embodiments, T1+T3≥4, so that when the first separator 40 and the first porous current collector 21 form a composite body 10B through the adhesive layer 42, the composite body 10B meets the structural strength requirements of the processing process as a whole.
[0090] See also Fig.10 In some embodiments, T2+T3≥4, so that the first separator 40 and the second porous current collector 31 form a composite body 10B through the adhesive layer 42, so that the composite body 10B meets the structural strength requirements of the processing steps as a whole.
[0091] In some embodiments, the tensile strength of the composite 10B along the width direction of the composite 10B is S1,160kgf / cm 2 ≤S1≤500kgf / cm 2 , so as to improve the structural stability of the composite 10B, facilitate the processing of the composite 10B as a whole, and reduce the risk of excessive adhesive clogging the pores and causing the lithium ion transmission path to fail.
[0092] Optionally, S1 is 160kgf / cm 2 、170kgf / cm 2 、180kgf / cm 2 、190kgf / cm 2 、200kgf / cm 2 、250kgf / cm 2 、300kgf / cm 2 、350kgf / cm 2 , 400kgf / cm 2 、450kgf / cm 2 、450kgf / cm 2 and 160kgf / cm 2 ≤S1≤500kgf / cm 2 Any other value in the range.
[0093] In some embodiments, the tensile strength of the composite 10B along the length direction of the composite 10B is S2, 160 kgf / cm 2 ≤S2≤500kgf / cm 2, so as to improve the structural stability of the composite 10B, facilitate the processing of the composite 10B as a whole, and reduce the risk of excessive adhesive clogging the pores and causing the lithium ion transmission path to fail.
[0094] Optionally, S2 is 160kgf / cm 2 、170kgf / cm 2 、180kgf / cm 2 、190kgf / cm 2 、200kgf / cm 2 、250kgf / cm 2 、300kgf / cm 2 、350kgf / cm 2 , 400kgf / cm 2 、450kgf / cm 2 、450kgf / cm 2 and 160kgf / cm 2 ≤S2≤500kgf / cm 2 Any other value in the range.
[0095] It should be noted that the tensile strength test process of the composite 10B is as follows: the test sample of the composite with a thickness of T μm is punched into 100 mm × 15 mm sheets along MD (length direction) / TD (width direction) with a die cutter, and then the sheet is perpendicular to the chuck of the high-speed rail tensile machine and the chuck is fixed and tightened with an initial height of 5 cm above and below, and the tensile rate is set to 50 mm / min, and the maximum tensile force is measured to be F. Tensile strength = F / 9.8 / (15 mm × T).
[0096] In some embodiments, the first porous substrate layer 41 includes at least one of polypropylene, polyethylene, polyethylene terephthalate, and polyimide.
[0097] In some embodiments, the porosity of the first porous substrate layer 41 is 30% to 45% to improve the liquid retention capacity of the first separator 40 , reduce the resistance of lithium ions passing through the first separator 40 , and help improve the structural strength of the first separator 40 .
[0098] See also Fig.11 One embodiment of the present application further provides an electronic device 200, which includes the battery cell 100 in any of the above embodiments. Optionally, the electronic device 200 may be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, an electric tool, etc.
[0099] In the above-mentioned battery cell 100 and electronic device 200, the first pole piece 20 includes a first porous current collector 21 and a first active material layer 22, and the first active material layer 22 is arranged only on one surface of the first porous current collector 21; the second pole piece 30 includes a second porous current collector 31 and a second active material layer 32, and the second active material layer 32 is arranged only on one surface of the second porous current collector 31; 4≤T1+T2+T3≤10, which can increase the transmission path of lithium ions and shorten the transmission distance of lithium ions, and is beneficial to improving the lithium ion transmission dynamics. Compared with the existing battery cell using non-porous metal foil, the internal resistance of the battery cell 100 can be reduced at the same single-sided coating weight, and the charge and discharge performance of the battery cell 100 can be improved.
[0100] The specific implementation of the battery cell 100 in the embodiment and the comparative example is described below.
[0101] 1. Rate capacity retention test At 25℃, the lithium-ion battery is charged to 4.3V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.3V, and left to stand for 10min; then discharged to 3.0V at a constant current of 0.2C, and left to stand for 15min. The above is one cycle, and the charge and discharge cycle is repeated 3 times, and the discharge capacity of these 3 cycles of 0.2C is recorded, and the average value is taken as the initial capacity Q0. The lithium-ion battery is charged to 4.3V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.3V, and left to stand for 10min; then discharged to 3.0V at a constant current of 10C, and left to stand for 15min. The above is one cycle, and the cycle is repeated 3 times, and the discharge capacity of these 3 cycles of 10C discharge is recorded, and the average value is taken as Q1, and the rate capacity retention rate of the lithium-ion battery is calculated.
[0102] The calculation formula for rate capacity retention rate is: Capacity retention rate (%) = Q1 / Q0 × 100%.
[0103] 2. Temperature rise test Place the battery cell at a test temperature of 25°C for 5 minutes, then charge it at a constant current of 5C to a voltage of 4.3V, and then charge it at a constant voltage of 0.05C; after standing for 2 hours to allow the temperature of the battery cell to drop to 25°C, discharge it at a constant current of 10C to a voltage of 3V. During the charging and discharging process, place a temperature sensor on the center surface of the lithium-ion battery, wrap the lithium-ion battery with thermal insulation cotton, and record the charging and discharging temperature rise during the charging and discharging process. For example, during the discharge process, record the temperature at the time of discharge completion, and subtract 25°C to obtain the 25°C discharge temperature rise (°C) of the battery cell.
[0104] Embodiment 1: A composite with a total thickness of 6.5 μm is selected, and the composite includes a first diaphragm and a porous copper foil and a porous aluminum foil bonded to both sides of the first diaphragm, wherein the thicknesses of the porous copper foil T1, the first diaphragm T3, and the porous aluminum foil T2 are 1.5 μm, 3 μm, and 2 μm, respectively, the porosity of the porous copper foil and the porous aluminum foil are both 30%, the average pore size of the pores of the porous copper foil and the porous aluminum foil is 2 μm, and the porosity of the first diaphragm is 40%.
[0105] The positive electrode uses NCM523 with a D50 of 6μm, the weight percentage of NCM523:PVDF:SP is 95:2.5:2.5, and the coating weight is 110mg / 1540.25mm 2 , coated on one surface of the porous aluminum foil to form a positive electrode material layer with a compaction density of 3.2 g / cm 3 .
[0106] The negative electrode uses artificial graphite with a D50 of 8μm, the weight percentage of graphite: SBR: CMC: SP is 96:1.2:0.8:2, and the coating weight is 60mg / 1540.25mm 2 , coated on one surface of the porous copper foil to form a negative electrode material layer with a compaction density of 1.4 g / cm 3 .
[0107] The first diaphragm is a PE diaphragm with a thickness of 3 μm. The porosity of the second diaphragm is 40%, and the second diaphragm is a PE diaphragm with a thickness of 3 μm.
[0108] In a dry argon atmosphere, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 20:30:40:10 to obtain an organic solvent, and then lithium salt LiPF6 is added to the organic solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0109] use Figure 5 The structure of the composite body and another diaphragm are assembled. Specifically, the size of the composite body is cut into 50 cm 2 ×50cm 2 , cut the first and second diaphragms into 55cm 2 ×55cm 2 The composite and the separator are stacked multiple times to form a 2Ah electrode assembly with a laminate structure.
[0110] The electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected (the injection amount is 6g), and a lithium-ion battery is obtained through vacuum packaging, static, formation, degassing, and trimming. Formation steps: charge to 3.3V at a constant current of 0.02C, and then charge to 3.6V at a constant current of 0.1C.
[0111] Example 2 It is basically the same as Example 1, except that the total thickness of the composite is 10 μm, and the thicknesses of the porous copper foil T1, the first separator T3, and the porous aluminum foil T2 are 3 μm, 4 μm, and 3 μm, respectively.
[0112] Example 3 It is basically the same as Example 1, except that the total thickness of the composite is 4 μm, and the thicknesses of the porous copper foil T1, the first separator T3, and the porous aluminum foil T2 are 0.5 μm, 3 μm, and 0.5 μm, respectively.
[0113] Example 4 It is basically the same as Example 1, except that the thicknesses of the porous copper foil T1, the first diaphragm T3, and the porous aluminum foil T2 are 1.4 μm, 3 μm, and 2.1 μm, respectively, and T2 / T1 is 1.5.
[0114] Example 5 It is basically the same as Example 1, except that the porosity of the porous copper foil and the porous aluminum foil is 20%.
[0115] Example 6 It is basically the same as Example 1, except that the porosity of the porous copper foil and the porous aluminum foil is 40%.
[0116] Example 7 The method is substantially the same as Example 1, except that the average pore size of the pores in the porous copper foil and the porous aluminum foil is 5 μm.
[0117] Example 8 The method is substantially the same as Example 1, except that the average pore size of the pores in the porous copper foil and the porous aluminum foil is 20 μm.
[0118] Embodiment 9: It is basically the same as Example 1, except that it includes two composites. Composite 1 includes a first diaphragm and a porous copper foil bonded to one side of the first diaphragm. The thicknesses of the porous copper foil T1 and the first diaphragm T3 are 1.5 μm and 3 μm, respectively. Composite 2 includes a first diaphragm and a porous aluminum foil bonded to one side of the first diaphragm. The thicknesses of the porous aluminum foil T1 and the first diaphragm T3 are 1.5 μm and 3 μm, respectively. Figure 7 The battery cell is prepared by using a structure of
[0119] Embodiment 10: It is basically the same as Example 1, except that along the thickness direction of the electrode assembly, the first separator is arranged between the negative electrode material layer and the positive electrode material layer (that is, the first separator is not compounded with the porous copper foil and the porous aluminum foil).
[0120] Comparative Example 1 It is basically the same as Example 1, except that the porosity of the copper foil and the aluminum foil is 0%.
[0121] Comparative Example 2 It is basically the same as Comparative Example 1, except that the thicknesses of the copper foil, the first diaphragm, and the porous aluminum foil are 4 μm, 6 μm, and 4 μm, respectively.
[0122] It can be seen from Comparative Example 1, Comparative Example 2, and Examples 1-10 that the first active material layer is set only on one surface of the first porous current collector, and the second active material layer is set only on one surface of the second porous current collector, and by adjusting the thickness, porosity or pore size of the first porous current collector, the second porous current collector, the first diaphragm, etc., the rate discharge capacity retention rate of the battery cell can be improved and the discharge temperature rise can be greatly reduced, which is beneficial to improving the charge and discharge performance of the battery cell.
[0123] The above description is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present application should be included in the disclosure scope of the present application.
Claims
1. A battery cell, characterized in that: The battery cell includes an electrode assembly, and the electrode assembly includes: A first pole piece, comprising a first porous current collector and a first active material layer, wherein the first active material layer is disposed only on one surface of the first porous current collector; A second pole piece, having a polarity opposite to that of the first pole piece, the second pole piece comprising a second porous current collector and a second active material layer, wherein the second active material layer is disposed only on one surface of the second porous current collector; A first diaphragm, disposed between the first pole piece and the second pole piece; The thickness of the first porous current collector is T1 μm, the thickness of the second porous current collector is T2 μm, the thickness of the first separator is T3 μm, and 4≤T1+T2+T3≤10.
2. The battery cell according to claim 1, characterized in that: 0.5≤T1≤3; and / or, 0.5≤T2≤3; and / or, 3≤T3≤5.
3. The battery cell according to claim 1, characterized in that: 4≤T1+T2+T3≤8.
4. The battery cell according to claim 3, characterized in that: 0.5≤T1≤2; and / or, 0.5≤T2≤2; and / or, 3≤T3≤4.
5. The battery cell according to any one of claims 1 to 4, characterized in that: The material of the first porous current collector includes copper, the material of the second porous current collector includes aluminum, and 1≤T2 / T1≤1.
6.
6. The battery cell according to any one of claims 1 to 5, characterized in that: The porosity of the first porous current collector is 20% to 40%, and the average pore size of the pores of the first porous current collector is D1 μm, 5≤D1≤20.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The porosity of the second porous current collector is 20% to 40%, and the average pore size of the pores of the second porous current collector is D2 μm, 5≤D2≤20.
8. The battery cell according to any one of claims 1 to 7, characterized in that: The electrode assembly further includes a second diaphragm, and the first electrode sheet, the first diaphragm, the second electrode sheet and the second diaphragm are stacked in sequence and then wound to form the electrode assembly; or, The second diaphragm, the first pole piece, the first diaphragm and the second pole piece are stacked in sequence and then wound to form the electrode assembly; or, The first pole piece, the first diaphragm and the second pole piece are stacked in sequence to form a repeating unit, a plurality of the repeating units are stacked in sequence to form the electrode assembly, and the second diaphragm is disposed between two adjacent repeating units.
9. The battery cell according to any one of claims 1 to 8, characterized in that: Along the thickness direction of the electrode assembly, the first separator is disposed between the first active material layer and the second active material layer; or, The first separator is disposed between the first porous current collector and the second active material layer; or, The first separator is disposed between the first active material layer and the second porous current collector; or, The first separator is disposed between the first porous current collector and the second porous current collector.
10. The battery cell according to any one of claims 1 to 9, characterized in that: The first diaphragm includes a first porous substrate layer and an adhesive layer disposed on at least one surface of the first porous substrate layer. The first diaphragm forms a composite with the first porous current collector and / or the second porous current collector via the adhesive layer.
11. The battery cell according to claim 10, characterized in that: The thickness of the composite is T4 μm, 4≤T4≤10.
12. The battery cell according to claim 10 or 11, characterized in that: The tensile strength of the composite body along the width direction is S1,160kgf / cm 2 ≤S1≤500kgf / cm 2 and / or, The tensile strength of the composite body along the length direction is S2, 160kgf / cm 2 ≤S2≤500kgf / cm 2 .
13. The battery cell according to any one of claims 10 to 12, characterized in that: The first porous substrate layer includes at least one of polypropylene, polyethylene, polyethylene terephthalate, and polyimide; The porosity of the first porous substrate layer is 30% to 45%.
14. The battery cell according to any one of claims 1 to 13, characterized in that: T1+T3≥4; and / or, T2+T3≥4.
15. An electronic device, characterized in that: The electronic device comprises the battery cell as claimed in any one of claims 1 to 14.